Accidents with biological material among undergraduate nursing students in a public Brazilian university - Reis,Renata Karina (2004)
During their academic activities, undergraduate nursing students are exposed to contamination by bloodborne pathogens, as well as by others found in body fluids, among which are the Human Immunodeficiency (HIV), Hepatitis B and C viruses. We developed a profile of victimized students, characterizing accidents with biological material occurring among undergraduate nursing students at a public university in São Paulo State, Brazil. We identified the main causes and evaluated the conduct adopted by students and their reactions and thoughts concerning the accidents. Seventy-two accidents were identified, of which 17% involved potentially contaminated biological material. Needles were the predominant cause of accidents. The most frequently involved topographic areas were the fingers. Only five students reported the accidents and sought medical care. Among these, two students were advised to begin prophylactic treatment against HIV infection by means of antiretroviral drugs. It was found that the risk of accidents is underestimated and that strategies such as formal teaching and continual training are necessary in order to make students aware of biosafety measures.